Aulas virtuales y su aporte en el pensamiento crítico - Ledesma Bermeo, Angel Delfin (2021)
One of the most important jobs as a teacher in the 21st century is teaching your students to think for themselves. No matter what subject or lesson you teach, at the end of the day the primary objective is for each of your students to acquire the necessary tools to solve any problem on their own, how to achieve it? Promoting critical thinking in them. Getting a student to obtain critical thinking is the goal that every teacher would like to achieve, but this is becoming difficult to meet due to various complications that are currently present, as an example this global pandemic that has quarantined most of the population worldwide. The little use and knowledge about ICT (Information and Communication Technologies) in education has created difficulties for students to achieve meaningful learning. A virtual classroom is a digital environment in which a knowledge exchange process can be carried out that aims to enable learning among the users who participate in the classroom. In other words, a virtual classroom is a space within an online platform in which teachers and students share content, and in which questions, doubts and evaluations of the participants are answered. As such, the virtual classroom has no physical or temporal limits. The student can access it whenever he wants to take his classes, without having to be subject to schedules and physical displacements.